Organizer of Training School - Koutinas, Michalis (My University, 2026)
Organizer of Training School – Agro-Industrial and Municipal Bio-organic Residues Valorization Towards Transition to a Sustainable Bio-Economy, Limassol, Cyprus, 3-4 October 2019.